1970
DOI: 10.1677/joe.0.0470183
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies on the Biosynthesis of Corticosteroids in Vitro From Exogenous Precursors by the Interrenal Glands of the Normal, Corticotrophin-Treated and Adenohypophysectomized Xenopus Laevis Daudin

Abstract: SUMMARY Incubation of the adrenocortical tissue of Xenopus with labelled steroidal precursors gave aldosterone, corticosterone, 11-deoxycorticosterone and 18-hydroxycorticosterone as the major products. Kinetic studies indicated that the major biosynthetic pathway in Xenopus is the same as that in the duck, cobra and frog, and follows the sequence: pregnenolone → progesterone → 11-deoxycorticosterone → corticosterone → aldosterone + 18-hydroxycorticosterone. The effects of adenohypophysectomy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1971
1971
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The sodium imbalance may be due to adrenocortical insufficiency leading to impaired extrarenal regulation (Fowler & Chester Jones, 1955;Myers, Bishop & Scheer, 1961). Chan & Edwards (1970) observed a diminished yield of corticosteroids from incubated adrenal glands of adenohypo¬ physectomized Xenopus. The renal effects of the operation suggest that there may be a reduced renal tubular reabsorption of sodium and potassium, but this does not lead to chronic imbalance of renal sodium loss since urine flow rate, and presumably glomerular filtration, was reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sodium imbalance may be due to adrenocortical insufficiency leading to impaired extrarenal regulation (Fowler & Chester Jones, 1955;Myers, Bishop & Scheer, 1961). Chan & Edwards (1970) observed a diminished yield of corticosteroids from incubated adrenal glands of adenohypo¬ physectomized Xenopus. The renal effects of the operation suggest that there may be a reduced renal tubular reabsorption of sodium and potassium, but this does not lead to chronic imbalance of renal sodium loss since urine flow rate, and presumably glomerular filtration, was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Although the renal actions of neurohypophysial hormones in Xenopus are in part 'amphibian' they do not include a clear-cut action on the renal tubular permeability to water (Henderson, Edwards, Garland & Chester Jones, 1972). On the other hand, the neurohypophysial and adrenocortical hormones chemically resemble those of amphi¬ bians rather than those of teleostean fishes (Follett & Heller, 1964;Chan & Edwards, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Corticosterone is typically referenced as the dominant and more abundant glucocorticoid in amphibians (Moore and Jessop, 2003; Norris and Carr, 2013; Wingfield and Romero, 2011), and occasionally listed as amphibians’ only glucocorticoid (Katsu and Iguchi, 2016). In the 1970s and 1980s, early studies about steroid synthesis reported production of corticosterone and little, if any, cortisol from isolated interrenal cells of frogs and toads in vitro (Chan and Edwards, 1970; Jolivet-Jaudet and Ishii, 1983; Jolivet-Jaudet and Leloup-Hatey, 1984; Mehdi and Carballeira, 1971). The results of these studies from just a few species of anurans (namely Bufo bufo, Rana catesbeiana , and Xenopus laevis ) led to a strong focus on corticosterone in the majority of studies on stress physiology in all amphibians.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the vast majority of studies on a popular aquatic model species, the clawed frog ( Xenopus sp. ), measure corticosterone (e.g., Jaudet and Hatey, 1984; Kulkarni and Buchholz, 2012; Shewade et al, 2020), likely based on results from in vitro studies with Xenopus laevis interrenal cells (Chan and Edwards, 1970; Jolivet-Jaudet and Leloup-Hatey, 1984). Moreover, cortisol has been detected in multiple species of amphibians (terrestrial and aquatic) using dermal swabs (Santymire et al, 2018), and cortisol increases in response to ACTH in terrestrial green treefrogs ( Hyla cinerea ), American toads ( Anaxyrus americanus ), and red-spotted newts ( Notophthalamus viridescens ) (Santymire et al, 2018).…”
Section: Introductionmentioning
confidence: 99%